The implementation of didactic strategies and materials in the classroom redirects the learning of the Spanish language - Toloza, Grace Fabiola; Machuca, Flor Stella Machuca (Rastros Rostros, 2023)
"The methodology of teaching the Spanish language is one of the most interesting chapters of didactics, since the success in the other school disciplines depends to a great extent on the good learning and mastery of the Spanish language". Spanish pedagogue Alberto del Pozo Pardo writes. For his part, the Colombian Luis Enrique Pachón says: "Knowing how to speak, listen, write and read the Spanish language is the key to academic success at any level".
Keywords: implementation; didactic; strategies; materials; classroom; Spanish language